Stumbling into sustainability: The effectual marketing approach of Ecuadorian entrepreneurs to reframe masculinity and accelerate the adoption of slow fashion. Issue 1 (1st October 2021) - Pohlmann, Attila; Muñoz-Valencia, Rodrigo
The prevalent business model of fast fashion has received widespread criticism for being antithetical to sustainability. Therefore, many Gen-Y fashion entrepreneurs routinely base their business models on principles of sustainability. Additionally, the green-feminine stereotype not only hinders male consumers' adoption of ecofriendly products but also poses cultural obstacles for male slow fashion entrepreneurs. By example of the Ecuadorian slow fashion company Remu Apparel, this article investigates how male entrepreneurs craft alternative masculinities through both personal and marketing narratives with the intent to mobilize the adoption of slow fashion and to overcome the aforementioned stereotype by reframing hegemonic masculinity. Interviews with the company's founders indicate that the causal fast fashion business model is recognized as harmful and unsustainable; consequently, a sustainability-oriented, effectual, slow fashion business approach is implemented, which opposes the globalized hegemonic business system and concurrently challenges and reframes traditional masculinity. Through respect for natural growth, intermittent compromises and career as self-discovery, an alternative, reflective masculinity is crafted and enshrined in Remu's business objectives. A visual content analysis indicates that social media tools are used to promote and stabilize the image of this alternative masculinity. The findings highlight avenues to mobilize slow fashion adoption within entrepreneurial networks and how sustainable, ecofriendly fashion can be promoted among male consumers.